Impact of Access to Electricity and Socio-Economic Environment on Poverty Reduction: An Empirical Study on Myanmar - Qian Xiong; Wenxin Shen; Chunna Liu; Xuteng Zhang; Wenzhe Tang; Colin F. Duffield; Felix Kin Peng Hui; Lihai Zhang (Energies)
Previous studies have identified the importance of access to electricity and the socio-economic environment for poverty reduction, but the comprehensive interplay and synergistic relationships between them remain unclear. Using data collected from Myanmar, this study establishes and tests conceptual models to explore the paths from access to electricity and socio-economic environment to capability and income poverty reduction. The results of structural equation modeling show that capability poverty reduction acts as a complete mediator between access to electricity and income poverty reduction, and plays a partial mediating role between socio-economic environment and income poverty reduction. Analysis of fuzzy-set qualitative comparative analysis demonstrates that lack of electricity is a key barrier impeding poverty alleviation efforts. Moreover, five effective configurations of poverty reduction factors are identified for Myanmar by considering the heterogeneity of different regions. This indicates that individual factors could not ensure a highly effective poverty reduction and different factors need to be appropriately configured for achieving the synergistic effects. These findings contribute to practical insights into poverty reduction policy making and sustainable development for developing countries.